2010
DOI: 10.4103/0972-9941.68579
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications in laparoscopic cholecystectomy: Incidence, mechanisms, prevention and management

Abstract: BACKGROUND:Laparoscopic cholecystectomy (LC) has established itself firmly as the ‘gold standard’ for the treatment of gallstone disease, but it can, at times, be associated with significant morbidity and mortality. Existing literature has focused almost exclusively on the biliary complications of this procedure, but other complications such as significant haemorrhage can also be encountered, with an immediate mortality if not recognized and treated in a timely manner.MATERIALS AND METHODS:Publications in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
2
54
0
10
Order By: Relevance
“…The most important patientrelated risk factors of operative bleeding are acute cholecystitis, liver cirrhosis, previous abdominal surgery, peritoneal adhesion and anatomical abnormalities [18][19][20]. Our data came in agreement with these results as we observed that operative bleeding was 7.84% in patients with acute cholecystitis, fibrotic gall bladder and extensive peritoneal adhesion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most important patientrelated risk factors of operative bleeding are acute cholecystitis, liver cirrhosis, previous abdominal surgery, peritoneal adhesion and anatomical abnormalities [18][19][20]. Our data came in agreement with these results as we observed that operative bleeding was 7.84% in patients with acute cholecystitis, fibrotic gall bladder and extensive peritoneal adhesion.…”
Section: Discussionsupporting
confidence: 90%
“…Incidence of operative bleeding in many series was up to 10% with an average figure of 2% [18]. The most important patientrelated risk factors of operative bleeding are acute cholecystitis, liver cirrhosis, previous abdominal surgery, peritoneal adhesion and anatomical abnormalities [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…19 The incidence of significant bleeding requiring conversion and that of wound infection was also not statistically different in the two groups. Over all morbidity rate was 8.3% in males and 6% in females and the difference was not statistically significant (p-value >0.5).…”
Section: Discussionmentioning
confidence: 75%
“…[22][23][24][25] which have mostly been proven not to be major concerns. [26][27][28] However, laparoscopic application to liver surgery was relatively delayed due to the complexity of the operation. Recently, two consecutive international consensus meetings made several points.…”
Section: Discussionmentioning
confidence: 99%